2016
DOI: 10.1016/j.msea.2016.08.057
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the single-phase constitutive relations of α/β dual phase TC6 titanium alloy

Abstract: The constitutive relations of α and β phases in a TC6 titanium alloy were determined by implementing a two-phase elastic-plastic self-consistent (EPSC) framework combined with the evolution of lattice strains; these strains were obtained via in-situ tensile loading synchrotron-based x-ray diffraction experiments. It was found that the {200} β reflection has the lowest stiffness and load partitions prior to the α phase during the elastic loading stage in this alloy. The simulated parameters including the diffra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Tan et al [ 12 ] and Holden et al [ 31 ] have argued that the hardness of micron-scale β phase was around three times higher than the micron-scale α phase. Shi et al [ 32 ] have observed that the stiffness of β phase was higher than α phase. Ankem et al [ 33 ] have demonstrated that the final strain of both α and β phases should be equal.…”
Section: Resultsmentioning
confidence: 99%
“…Tan et al [ 12 ] and Holden et al [ 31 ] have argued that the hardness of micron-scale β phase was around three times higher than the micron-scale α phase. Shi et al [ 32 ] have observed that the stiffness of β phase was higher than α phase. Ankem et al [ 33 ] have demonstrated that the final strain of both α and β phases should be equal.…”
Section: Resultsmentioning
confidence: 99%
“…When using EPSC methods on two-or multiphase materials with high fractions of contributing phases, the question of the interaction of the two or more phases with each other has to be taken into account. It is known from the literature (e.g., [52][53][54][55][56]) that this should be best implemented by considering the changing stiffnesses due to the interaction of the two phases or the elasto-plastic stiffness modulus.…”
Section: Elasto-plastic Self-consistent Modelmentioning
confidence: 99%